Impacto del crecimiento urbano y su incidencia en el crecimiento económico de los pequeños negocios de la parroquia Venus del Rio del cantón Quevedo; periodo 2012 - Macías Malats, Luis Vicente (2013)
Urban growth is geographical expansion of a city, its population increases due to economic growth, increased housing and buildings for business and industry to the periphery.The geographic space as an object of study of geography, is an integrated set of elements such natural physical, socio-economic and cultural. There man has important functions, high-impact, linked to its scope, comprised of all activities and human structures that describe the territory.